Population genetic structure of Bellamya aeruginosa (Mollusca: Gastropoda: Viviparidae) in China: weak divergence across large geographic distances. Issue 21 (13th October 2015) - Gu, Qian H.; Husemann, Martin; Ding, Baoqing; Luo, Zhi; Xiong, Bang X.
Abstract: Bellamya aeruginosa is a widely distributed Chinese freshwater snail that is heavily harvested, and its natural habitats are under severe threat due to fragmentation and loss. We were interested whether the large geographic distances between populations and habitat fragmentation have led to population differentiation and reduced genetic diversity in the species. To estimate the genetic diversity and population structure of B. aeruginosa, 277 individuals from 12 populations throughout its distribution range across China were sampled: two populations were sampled from the Yellow River system, eight populations from the Yangtze River system, and two populations from isolated plateau lakes. We used seven microsatellite loci and mitochondrial cytochrome oxidase I sequences to estimate population genetic parameters and test for demographic fluctuations. Our results showed that (1) the genetic diversity of B. aeruginosa was high for both markers in most of the studied populations and effective population sizes appear to be large, (2) only very low and mostly nonsignificant levels of genetic differentiation existed among the 12 populations, gene flow was generally high, and (3) relatively weak geographic structure was detected despite large geographic distances between populations. Further, no isolation by linear or stream distance was found among populations within the Yangtze River system and no signs of population bottlenecks were detected. Gene flow occurred even between far distant populations, possibly as a result of passive dispersal during flooding events, zoochoric dispersal, and/or anthropogenic translocations explaining the lack of stronger differentiation across large geographic distances. The high genetic diversity of B. aeruginosa and the weak population differentiation are likely the results of strong gene flow facilitated by passive dispersal and large population sizes suggesting that the species currently is not of conservation concern. Abstract : High levels of intra‐population genetic diversity and low inter‐population differentiation was found in Bellamya aeruginosa in China. Population sizes were intermediate to large and levels of gene flow were high suggesting that both gene flow and population size help to maintain high genetic variation. Gene flow occurred even between far distant populations, likely as a result of passive dispersal during flooding events, zoochoric dispersal and possibly anthropogenic translocations.